ВЛИЯНИЕ ПРОБИОТИКА РИОФЛОРА БАЛАНС НЕО НА МЕТАБОЛИЧЕСКУЮ АКТИВНОСТЬ МИКРОФЛОРЫ КИШЕЧНИКА - И. А. Ли; С. Ю. Сильвестрова; Е. В. Трейман; В. Н. Дроздов (Архивъ внутренней медицины)
Having studied the influence of the modern complex of probiotic RioFlora Balance Neo on intestinal microbiota metabolism, the authors concluded that the use of RioFlora Balance Neo restore normal microflora metabolism by stimulating the synthesis of essential functions of the intestine short-chain fatty acids. A significant advantage of probiotic RioFlora Вalance Neo is activation of synthesis of butyrate (butyric acid) — the most important product life of the intestinal microflora, that regulates proliferation of the intestinal mucosa, and provides natural oncoprotective effect.